Primary malignant melanoma of the esophagus: a population-based study - Chen, Jiayan; Wen, Junmiao; Xu, Xinyan; Liu, Di; Huang, Lv; Fan, Min (Translational Cancer Research, 2018)
Background: Primary malignant melanoma of the esophagus (PMME) is an extremely rare neoplasm with a dismal prognosis. Only a few individual cases from Asian populations have been reported; the clinicopathological features and survival outcomes for Western patients remain unclear. In this study, we aimed to fill this gap in knowledge using the Surveillance, Epidemiology, and End Results (SEER) database. Methods: A population cohort study was conducted using data extracted from the SEER database for PMME patients from 1973 to 2014; the data included characteristics, treatment and outcomes. Results: A total of 55 patients with PMME were included. The average patient age was 71.8±13.6. The majority of them were female (56.4%) and Caucasian (87.3%). The tumors were located mainly in the middle to lower thoracic esophagus (38, 69%). Sixteen patients were categorized as having a distant stage, whereas 31 had early stage (localized or regional). The median OS was 9 months, and the 1-, 3-year OS was 36.4% and 7.3%. Unfortunately, no case with a survival of more than 5 years was found. The OS of PMME was the worst compared with that of other types of esophageal neoplasms. The survival outcome of PMME patients resembled those of squamous cell carcinoma (SQ) patients but inferior to those of patients with adenocarcinoma (AD) of the esophagus. Most of the PMME patients were treated with surgical resection (33, 60%), and 14 received radiotherapy. Surgical resection was performed for most of the early stage PMME patients (24/31, 77.4%). Multivariate Cox analysis showed that females and those who underwent radical esophagectomy had a better OS. Conclusions: PMME is an extremely rare disease with a poorer prognosis than other esophageal histological types. Most of the PMME patients were female and Caucasian and had been diagnosed with early-stage disease. Radical surgical resection might be an effective approach for treating PMME. More cases with adequate information are needed to understand PMME better.